Cymothoa hermani sp. nov. (Isopoda, Cymothoidae, Crustacea), a parasitic isopod, collected off the Zanzibar coast, Tanzania from the mouth of a parrotfish (Scaridae) - Hadfield, Kerry A.; Bruce, Niel L.; Smit, Nico J. (Zootaxa, 2011)
Cymothoa hermani sp. nov., a buccal fish-parasitic isopod is described from off Unguja Island, Zanzibar, from the buccal cavity of the marbled parrotfish, Leptoscarus vaigiensis. Cymothoa hermani sp. nov. is characterised by the unique bulbous ornamentation on pereonite 1, anterolateral angles on pereonite 1 rounded and produced past frontal margin of cephalon, and pereopods with long and slender dactyli. There are no other species of Cymothoa known from parrotfishes. This description increases the number of known Cymothoa from the southwestern Indian Ocean to four.